2015
DOI: 10.1111/clr.12564
|View full text |Cite
|
Sign up to set email alerts
|

Use of short implants (6 mm) in a single‐tooth replacement: a 5‐year follow‐up prospective randomized controlled multicenter clinical study

Abstract: The results of this study showed that 6-mm-long implants supporting single crowns loaded within 7 weeks from installation lose a small amount of marginal bone during 5 years of functional loading, similar to that of 10-mm-long implants. However, a higher degree of implant loss was recorded at the short implants, probably due to the fracturing of the surrounding bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
210
7
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(247 citation statements)
references
References 34 publications
(36 reference statements)
25
210
7
5
Order By: Relevance
“…However, Rossi and colleagues reported that a lower survival rate of 86.7% was observed at the 6 mm-long, 4.1 mm-diameter implants supporting single crowns loaded within 7 weeks when compared with the same diameter 10 mm-long implants, which was 96.7%. 20 Most of the studies on the topic of short implants proposed that short implants may be splinted with either short or long implants. 25,30,31 Nevertheless, there is no evidence for such and longer OsseoSpeed implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Rossi and colleagues reported that a lower survival rate of 86.7% was observed at the 6 mm-long, 4.1 mm-diameter implants supporting single crowns loaded within 7 weeks when compared with the same diameter 10 mm-long implants, which was 96.7%. 20 Most of the studies on the topic of short implants proposed that short implants may be splinted with either short or long implants. 25,30,31 Nevertheless, there is no evidence for such and longer OsseoSpeed implants.…”
Section: Discussionmentioning
confidence: 99%
“…Limited literature can be found for the short implant in an early loading protocol. 13,[19][20][21][22] Consequently, traditional loading remains the choice of most clinicians.…”
mentioning
confidence: 99%
“…Short implants were classified as those < 10 mm. 38 From 2014, some randomized clinical trials with short implants and standard implants were carried out in posterior single crowns, [39][40][41] which instigated the elaboration of this review. 35,36 With the evolution and better performance of these implants, there is a tendency to include a new class of implants-ultra short implants ≤ 6 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The use of dental implants as intraosseous supports for different designs of prosthetic constructions demonstrates high rates of success both in 5 and in 10 years prospective [1][2][3][4]. Such method of treating the patients with symptoms of partial and full adentia, according to previous studies, usually exceeds 90% level of success [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%